Surfactant protein-D, a potential mediator of inflammation in axial spondyloarthritis. (2nd July 2018) - Munk, Heidi L; Fakih, Dalia; Christiansen, Lene; Tan, Qihua; Christensen, Anne F; Ejstrup, Leif; Loft, Anne G; Junker, Kirsten; Kyvik, Kirsten O; Jounblat, Rania; Holmskov, Uffe; Sorensen, Grith L; et al.
Abstract: Objectives: Surfactant protein-D (SP-D), an innate immune defence molecule of the collectin family, is expressed in lungs and additional extrapulmonary epithelia. SP-D has immune modulatory and anti-microbial effects depending on its oligomerization. The ratio of high molecular weight (HMW): low molecular weight (LMW) SP-D in serum is mainly determined by the Met11Thr polymorphism (SNP rs721917). We aimed to study the SP-D serum level and the molecular size distribution in patients with untreated axial spondyloarthritis (axSpA) as compared with control subjects. Methods: Thirty-four patients with disease modifier untreated axSpA according to the ASAS criteria, age 19–63 years, disease duration 3.9 (2.2–5.6) years were included. Demographics, smoking habits, HLA-B27 status, ASDAS, BASDAI, BASFI, BASMI and visual analogue scale scores were recorded. SP-D in serum was measured by ELISA. DNA was isolated from whole blood and single nucleotide polymorphism rs721917 was genotyped. SP-D molecular size distribution was determined using gel filtration chromatography. Results: SP-D in serum did not differ between patients with axSpA and healthy controls, 1177 (869, 1536) vs 910 (494, 1682) (P = 0.35) and SP-D did not correlate with disease activity. However, the HMW/LMW ratio of SP-D in serum was significantly lower in axSpA, 0.38 (0.18, 0.53) compared with controls 1.49 (0.37, 3.24) when adjusting for the Met11Thr polymorphism, gender, age, BMI and smoking (P = 0.0004). There was no correlation between HMW/LMW ratio and CRP or composite diseases outcome measures. Conclusion: We suggest that predominance of LMW oligomeric variants of SP-D may enhance local or systemic inflammatory responses in axSpA.